Addition of Dexmedetomidine to the Anesthesia Regimen Attenuates Pain and Improves Early Recovery After Esophageal Endoscopic Submucosal Dissection: A Randomized Controlled Trial - Luo X; Hou HJ; Chen PS; Chang XL; Li Y; An LX; Liu FK; Xue FS (Dove Medical Press, 2024)
Xin Luo,1,* Hai-Jun Hou,2,* Pei-Shan Chen,1 Xin-Lu Chang,1 Yang Li,1 Li-Xin An,1 Fu-Kun Liu,1 Fu-Shan Xue1,3 1Department of Anesthesiology, Beijing Friendship Hospital, Capital Medical University, Beijing, People's Republic of China; 2Department of Pain Medicine, Guanganmen Hospital, China Academy of Chinese Medical Sciences, Beijing, 100053, People's Republic of China; 3Department of Anesthesiology, Shengli Clinical Medical College of Fujian Medical University, Fujian Provincial Hospital, Fuzhou University Affiliated Provincial Hospital, Fuzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Fu-Shan Xue, Department of Anesthesiology, Shengli Clinical Medical College of Fujian Medical University, Fujian Provincial Hospital, Fuzhou University Affiliated Provincial Hospital, Fuzhou, Fujian Province, 350001, People's Republic of China, Tel +86-13911177655, Fax +86-0591-88217841, Email xuefushan@aliyun.com; fushanxue@outlook.comObjective: Postoperative pain is a common yet often underestimated complication following esophageal endoscopic submucosal dissection (ESD), with limited strategies for effective management. This prospective, double-blind, randomized controlled trial assessed the effects of adding dexmedetomidine (DEX) to the anesthesia regimen on postoperative pain and early recovery in patients undergoing esophageal ESD.Methods: In total, 60 patients scheduled for elective esophageal ESD under general anesthesia were randomly assigned to the DEX or control group. The DEX group received an intravenous loading dose of DEX at 1 μg/kg for 10 min, followed by a continuous intravenous infusion of 0.6 μg/kg/h, which was stopped 30 min before the end of the procedure. The control group received normal saline as a placebo. The study's primary outcome was the incidence of moderate-to-severe postoperative pain. Secondary outcomes included postoperative pain scores, hemodynamic parameters, the occurrence of postoperative nausea and vomiting (PONV), patient satisfaction, and lengths of stay in the post-anesthesia care unit (PACU) and hospital.Results: The incidence of moderate-to-severe postoperative pain in the DEX group was significantly lower than that in the control group (absolute difference: − 33.4%; OR: 0.250; 95% CI: 0.085- 0.731, P = 0.01). Pain scores at 1 h postoperatively (0.5[2.0] vs 3.0[1.3], P = 0.003) were significantly lower in the DEX group. Additionally, morphine dosage in the PACU (0[0] vs 1.0[2.0] P = 0.004) was significantly reduced in the DEX group compared with the control group. In the DEX group, the incidence and severity of PONV were significantly decreased and the length of PACU stay was shorter than in the control group (P